The Palgrave Handbook of Relational Sociology (Springer International Publishing, 2018)
This handbook on relational sociology is about a rapidly growing approach in the social sciences; an approach which is connected to the interests of a large, diverse pool of researchers across a range of disciplines.The book aims to elucidate the complexity and the scope of this growing approach by dealing with three central questions: where does relational sociology come from and what are its principal concerns? What are the main theoretical and methodological currents within relational sociology? What have we studied in relational sociology and what are the results? Relational sociology has been one of the key foundations of the 'relational turn' in human sciences since the 1980s, and offers the opportunity to redefine the basic epistemological and ontological principles of sociology as we know it. .